2014
DOI: 10.1080/21711976.2014.942509
|View full text |Cite
|
Sign up to set email alerts
|

Gender, masculinity and femininity as ecocentrism and anthropocentrism predictors / Género, masculinidad y feminidad como predictores del ecocentrismo y el antropocentrismo

Abstract: The objective of this study is to analyse the function of gender-role orientation (masculinity and femininity) versus gender (man and woman) in explaining anthropocentric and ecocentric beliefs based on the Spanish version of the NEP scale. 116 university students of both genders participated in the study (Men: 51; Women: 65). The NEP scale and the BSRI were used. Covariance and stepwise hierarchical regression analyses were conducted. The results suggest that, while anthropocentrism is predicted by gender and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
(172 reference statements)
0
7
0
6
Order By: Relevance
“…My colleagues and I have examined variables that could explain this sex difference, and our findings indicate female participants tend to display higher levels of environmental protection because they were higher in Agreeableness and Conscientiousness while lower in SDO compared to male participants (Desrochers et al, 2019;Graça et al, 2018;Jylhä, Cantal, Akrami, & Milfont, 2016;. Future research should explore this further and examine the extent to which gender identification (not only biological sex) is related to environmental protection (e.g., Calvo-Salguero et al, 2014;Desrochers et al, 2019, Study 3). Gender perspectives are also a DIFFERENTIAL PSYCHOLOGY AND ENVIRONMENTALISM 18 very important topic within environmental psychology research more broadly (Cortés, 2014), and should be explored further.…”
Section: Personological Roots Of Environmental Protection/exploitationmentioning
confidence: 67%
“…My colleagues and I have examined variables that could explain this sex difference, and our findings indicate female participants tend to display higher levels of environmental protection because they were higher in Agreeableness and Conscientiousness while lower in SDO compared to male participants (Desrochers et al, 2019;Graça et al, 2018;Jylhä, Cantal, Akrami, & Milfont, 2016;. Future research should explore this further and examine the extent to which gender identification (not only biological sex) is related to environmental protection (e.g., Calvo-Salguero et al, 2014;Desrochers et al, 2019, Study 3). Gender perspectives are also a DIFFERENTIAL PSYCHOLOGY AND ENVIRONMENTALISM 18 very important topic within environmental psychology research more broadly (Cortés, 2014), and should be explored further.…”
Section: Personological Roots Of Environmental Protection/exploitationmentioning
confidence: 67%
“…Finally, the revised EAS scale was administered a second time, which enabled us to confirm the factor structure of the scale in the Spanish sample. We should mention that given the fact that the number of females in the sample of this study was higher than the number of males, we wondered whether this particularity in the sample might somehow affect the scores on the EAS, since some studies found differences with regard to the degree to which gender may influence different variables related to environmental behaviour (Calvo-Salguero, Aguilar-Luzón, Salinas, & García, 2014; Ruiz, Marrero, & Hernández, 2018). Therefore, we decided first to clarify how this composition may affect our data.…”
Section: Discussionmentioning
confidence: 95%
“…Finalmente, una segunda administración de la escala EACA ya revisada, permitió confirmar la estructura factorial de la escala en la muestra española. Cabe mencionar que dado que el número de mujeres que componían la muestra de este estudio era superior al número de hombres, nos planteamos si esta particularidad en la muestra utilizada podría afectar de algún modo a las puntuaciones de la EACA, pues algunos estudios encuentran diferencias respecto al grado en el que el género puede influenciar a diversas variables antecedentes del comportamiento ambiental (Calvo-Salguero, Aguilar-Luzón, Salinas, & García, 2014; Ruiz, Marrero, & Hernández, 2018). Así pues, decidimos en primer lugar, esclarecer cómo esta composición podía afectar a nuestros datos.…”
Section: Discussionunclassified
“…However, as pointed out by Amérigo, Aragonés, and García (2012), this variable yields contradictory results when the measurement of pro-environmental attitude and behaviour is considered from a multidimensional perspective. The recent review carried out by Calvo-Salguero et al (2014) also reports contradictory results in samples of adults. Research conducted with children reveals similarly ambiguous results, with some papers finding no differences (Manoli et al, 2007), and others that do observe differences (Juárez-Lugo, 2010; Vázquez & Manassero, 2005; Zelezny et al, 2000).…”
mentioning
confidence: 99%
“…Another factor that generates a high volume of research in relation with attitudes towards the environment is gender, using this term in favour of the concept of ‘sex’ in the sense described by Calvo-Salguero, Aguilar-Luzón, Salinas, and García-Martínez (2014) at the start of their article. In this regard, there is research conducted with adults that frequently reports greater environmental concern among women (Zelezny, Chua, & Aldrich, 2000).…”
mentioning
confidence: 99%